Incidence and prognosis of gastroesophageal cancer in rural, urban, and metropolitan areas of the United States. Issue 22 (20th August 2013) - Wang, Zhensheng; Goodman, Michael; Saba, Nabil; El‐Rayes, Bassel F.
Abstract : BACKGROUND: The objective of this study was assess differences in the incidence, late‐stage diagnosis, and prognosis of squamous cell carcinoma of the esophagus (SCCE), adenocarcinoma of the esophagus (AE), and adenocarcinoma of the gastric cardia (AGC) in metropolitan, urban, and rural areas in the United States. METHODS: The authors identified 29, 527 patients with SCCE, AE, or AGC who were reported to the Surveillance, Epidemiology, and End Results Program between 2004 and 2009. Incidence estimates for each malignancy were compared across metropolitan, urban, and rural areas. Multivariable logistic regression models were applied to evaluate the association between residential setting and late (distant‐stage) diagnosis, and the results were reported as adjusted odds ratios and 95% confidence intervals (CIs). Cox proportional hazard models were used to examine the association between residential setting and cause‐specific survival. RESULTS: When residential setting was analyzed using metropolitan population centers as the reference category, the incidence of AE was higher in urban areas (rate ratio [RR], 1.13; 95% CI, 1.06‐1.20) and rural areas (RR, 1.15; 95% CI, 1.05‐1.25), whereas the incidence of SCCE was lower in rural areas (RR, 0.80; 95% CI, 0.70‐0.91). Rural patients were less likely to be diagnosed with stage IV AE compared with patients residing in metropolitan areas (odds ratio, 0.79; 95% CI, 0.65‐0.97). No differences in prognosis were observed when patients from large metropolitan centers were compared with their rural counterparts. CONCLUSIONS: The current findings indicated that preconceptions regarding disparities in the time of diagnosis and survival between patients from metropolitan and rural areas in the United States are either unwarranted or out of date, at least with respect to gastroesophageal cancers. Cancer 2013 ;119:4020–4027. © 2013 American Cancer Society . Abstract : Cancers located in gastroesophageal sites are expected to have different incidence and outcomes based on the patient's area of residence. The results from this study suggest that the preconceptions about urban/rural disparities in relation to gastroesophageal cancers in the United States are either unwarranted or out of date.